Qualitative research in the Arabic language. When should translations to English occur? A literature review - Nouf M. Aloudah (Elsevier, 2022)
Qualitative studies are a valuable approach to exploratory research. Frequently, researchers are required to collect data in languages other than English, which requires a translation process for the results to be communicated to a wider audience. However, language-embedded meaning can be lost in the translation process, and there is no consensus on the optimum timing of translation during the analysis process. Thus, the aim of this paper was to review how researchers conduct qualitative research with Arabic-speaking participants and the timing of data translation.Three databases were searched (PubMed, Scopus, and Web of Science) for the period January 2010 to January 2020. Studies were excluded if the data collection was not in Arabic or the study was not qualitative or healthcare related.Thirty-one studies were included, 26 of which translated all transcripts into English and then analyzed the data in English. Five studies transcribed the data in Arabic, analyzed it in Arabic, and then translated the results to English or conducted a parallel analysis. The reason provided for translating the data into English before the analysis was to enable non-Arabic authors to access the data and assist with the analysis. The search results suggest that researchers prefer translating data before analyzing it and are aware of the possibility of losing meaning during the translation process, which might affect the results. A more thoughtful approach to the timing of translation should be undertaken to ensure the subtleties of language are not lost during the analysis of qualitative data.